HUBUNGAN IgG DAN IgM DENGUE TERHADAP JUMLAH TROMBOSIT PADA PASIEN DEMAM BERDARAH DENGUE DI RUMAH SAKIT PENDIDIKAN PROF.dr.CHAIRUDDIN PANUSUNAN LUBIS UNIVERSITAS SUMATERA UTARA - Ice Ratnalela Siregar; Muhammad Iqbal (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
The immune responses that play a role in DHF cases are Immunoglobulin M (IgM) and Immunoglobulin G (IgG). In primary Dengue infection, IgM begins to form and is detected on the third to fifth day, whereas in secondary Dengue infection, IgG levels will increase and then remain in the human body with low titers for life. Thrombocytopenia occurs in DHF patients due to antigen-antibody reactions and activation of the complement system which causes deposition of IgM and IgG immune cells on the surface of platelet cells. This causes reticuloendothelial cells to destroy platelets so that DHF patients will experience thrombocytopenia. To find out the analysis of dengue IgG and IgM examination on the results of platelet counts in dengue hemorrhagic fever patients at Prof. Teaching Hospital. dr. Chairuddin Panusunan Lubis, University of North Sumatra. The research used is descriptive quantitative. The examination method used is Dengue IgG and IgM Dengue Rapid Test, Platelet Count Examination using a Hematology Analyzer. The number of respondents is 11 samples taken by total sampling technique. Based on the results of a study of Dengue IgG and IgM in Dengue Hemorrhagic Fever patients at Prof. Teaching Hospital. dr. Chairuddin Panusunan Lubis, University of North Sumatra who had IgG + and IgM levels - more, namely 10 (92%) patients, IgG - and IgM + as many as 1 (8%) patients. Based on the number of platelets obtained in Dengue Hemorrhagic Fever patients at Prof. Teaching Hospital. dr. Chairuddin Panusunan Lubisa, University of North Sumatra, which decreased by 9 patients, and there were some who had normal platelet counts of 2 patients. There is no relationship between Dengue IgG and IgM on platelet count in Dengue Hemorrhagic Fever patients.